Preparation method of polyaspartic acid-carboxymethyl cellulose double-network hydrogel water-retaining agent

The construction of a dual network hydrogel by the composite and hydrogen bond crosslinking method of polyaspartic acid and carboxymethylcellulose solves the problem of difficult degradation and insufficient mechanical properties of existing water retention agent materials, and achieves efficient swelling, water retention and biodegradation properties.

CN119875147APending Publication Date: 2025-04-25ZHEJIANG GONGSHANG UNIVERSITY

Patent Information

Application Number
CN202411858722.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing agricultural water retention agent materials such as polyacrylamide are difficult to degrade, resulting in environmental pollution. At the same time, polyaspartic acid hydrogels have shortcomings in mechanical properties, which limits their application in the field of water retention agents.

Method used

A double network hydrogel is constructed by hydrogen bond cross-linking method to enhance the mechanical properties and water retention ability of the gel.

Benefits of technology

It has achieved the improvement of the mechanical properties of polyaspartic acid hydrogels, and has excellent swelling performance, water retention performance and biodegradability. It is suitable for water retention agent applications in the agricultural and forestry field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119875147A_ABST
    Figure CN119875147A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of water-retaining agents, and particularly relates to preparation of a hydrogel water-retaining agent. The invention provides a preparation method of a polyaspartic acid-carboxymethyl cellulose double-network hydrogel water-retaining agent, which comprises the following steps: 1) preparation of macromolecular polysuccinimide: carrying out thermal shrinkage polymerization reaction by utilizing phosphoric acid and aspartic acid, and then carrying out post-treatment to obtain polysuccinimide; and 2) preparation of polyaspartic acid-carboxymethyl cellulose hydrogel: adding carboxymethyl cellulose (CMC) and ethylene glycol diglycidyl ether into the polyaspartic acid gel liquid, pouring the obtained viscous gel mixed liquid into a mold, and standing to obtain gel. By adopting the method disclosed by the invention, the double-network hydrogel with excellent swelling property, mechanical property and water retention property can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of water retaining agents, and particularly relates to the preparation of a hydrogel water retaining agent. Background Art

[0002] Water is one of the important factors in agricultural production, but the global shortage and uneven distribution of water resources have restricted the sustainable development of agriculture. Agricultural water retainer is an important water-saving product with good water absorption and water retention properties. It can improve soil moisture utilization and reduce irrigation times. It is widely used in agriculture, forestry and other fields. Currently, the most developed and used water retainer materials are mainly polyacrylic acid (PAAc) and polyacrylamide (PAAm). They have good water absorption properties and simple synthesis processes, but they cannot be completely degraded naturally. The remaining waste causes secondary pollution to the environment, and they are non-environmentally friendly materials. [1-2] .

[0003] Polyaspartic acid (PASP) is a polyamino acid formed by combining D-aspartic acid or L-aspartic acid through amide bonds formed by α-amino and α-carboxyl or β-carboxyl groups. The amide bonds on the main chain of polyaspartic acid are easily broken by microorganisms and fungi, and finally degraded into water and carbon dioxide that are harmless to the environment. It is a non-toxic, pollution-free, biodegradable, environmentally friendly green chemical. Polyaspartic acid has a wide range of uses, and researchers have used it to develop various biological and medical materials including tissue engineering and drug / gene delivery. Cross-linking polyaspartic acid can obtain PASP hydrogels that present a spatial network structure at the microscopic level. PASP hydrogels have good water absorption and water retention properties, and are considered to be a new type of green material with the most potential to replace polyacrylic acid or polyacrylamide water-retaining agents, and have broad application prospects in the fields of agriculture and forestry. [3-4] . Professor Lv Shaoyu's team from Lanzhou University [5] A composite superabsorbent resin containing PASP, hydroxyethyl polysuccinimide (PHEA), konjac mannan, acrylic acid and acrylamide was synthesized, and it was found that the resin can effectively improve the water retention capacity of the soil, and the water retention rate of the soil is still as high as 81.8% after 23 days. Although PASP has natural advantages, at present, when used as a water retaining agent, it still needs to be used in combination with acrylic acid or acrylamide in most cases. This is because PASP hydrogel has certain deficiencies in strength, elasticity and toughness, which limits the application of PASP hydrogel in agricultural and forestry water retaining agents.

[0004] Recently, researchers have found that double network hydrogels (DN hydrogels) have great advantages in mechanical properties. [6]One of the networks of the DN hydrogel is highly cross-linked but easily breaks during deformation, while the other network is less cross-linked but has good network elasticity. During deformation, the brittle network of the DN gel breaks internally and dissipates most of the energy, so that cracks do not expand too early or too quickly. The bonds that break inside the brittle network are called sacrificial bonds. Professor Gong Jianping of Hokkaido University and others [7] The toughening mechanism of DN gel is believed to be based on sacrificial bonds and the unfolding of ordered domains within the organic components of the gel-like tissue. In biological materials such as living tissues, most of the sacrificial bonds are reversible non-covalent bonds such as hydrogen bonds, electrostatic interactions, hydrophobic interactions, and host-guest interactions.

[0005] Cellulose, as the most abundant renewable resource on earth, will become the main chemical resource in the future. [8] . Carboxymethyl cellulose (CMC) is a cellulose molecule with carboxymethyl groups introduced at the hydroxyl position. CMC shows great potential because it is derived from natural and renewable resources, making it environmentally friendly. Carboxymethyl cellulose contains a large number of hydroxyl and carboxyl groups, which can spontaneously cross-link into a hydrogen bond network, playing the role of sacrificial bonds [9] .

[0006] The invention of CN113004545A, "A method for preparing a polyaspartic acid semi-interpenetrating nanocomposite hydrogel", informs: Step 1, maleic anhydride is added to distilled water, hydrolyzed in an oil bath, ammonia water is added, stirred and reacted to obtain an intermediate solution; Step 2, montmorillonite is dispersed in distilled water, and the intermediate solution, H3PO4 solution, and KH550 solution are added to the montmorillonite suspension in sequence, ultrasonically dispersed and dried to obtain an intermediate product, crushed, hydrolyzed with NaOH solution after adding distilled water, and then neutralized with HCl solution, poured into a saturated solution of sodium chloride-methanol for precipitation, filtered, dried, and ground to obtain a polyaspartic acid-montmorillonite composite material; Step 3, prepare a carboxymethyl cellulose solution, weigh the polyaspartic acid-montmorillonite composite material and disperse it in distilled water, extract the carboxymethyl cellulose solution and add it thereto, mix, and freeze-dry to obtain a polyaspartic acid-montmorillonite semi-interpenetrating nanocomposite hydrogel. Its advantages are: simple preparation process and low preparation cost. However, the hydrogel prepared by this method uses a large amount of organic reagents during the operation process, and the mechanical properties are lower than those of this patent and it is not designed as a double network structure hydrogel.

[0007] References:

[0008] [1] Tan Tianwei, Yu Jianliang, Zhang Xu. (2011). New progress in biorefining technology research. Chemical Industry Progress, 30(1), 117–125.

[0009] [2] Du Changwen, Zhou Jianmin. (2002). Research and development of controlled release fertilizers. Soil, 34, 127–133.

[0010] [3] Adelnia, H., Tran, HDN, Little, PJ, Blakey, I., & Ta, HT (2021). Poly(aspartic acid) in Biomedical Applications: From Polymerization, Modification, Properties, Degradation, and Biocompatibility to Applications. ACS Biomaterials Science & Engineering, 7(6), 2083–2105.

[0011] [4]Das,P.,&Jana,NR(2021).Biomedical Applications of FunctionalPolyaspartamide-Based Materials.ACSApplied Polymer Materials, 3(10),4791–4811.

[0012] [5] Lü, S., Feng, C., Gao, C., Wang, X., Xu, X., Bai,

[0013] [6]Suzuka,J.,Tsuda,M.,Wang,L.,Kohsaka,S.,Kishida,K.,Semba,S.,Sugino,H.,Aburatani,S.,Frauenlob,M.,Kurokawa,T.,Kojima,S.,Ueno,T.,Ohmiya,Y.,Mano,H.,Yasuda,K.,Gong,J.P.,&Tanaka,S.(2021).Rapidreprogramming of tumour cells intocancer stem cells on double-network hydrogels.Nature BiomedicalEngineering,5(8),914–925.

[0014] [7]Haque,Md.A.,Kurokawa,T.,&Gong,J.P.(2012).Super tough doublenetwork hydrogels and theirapplication as biomaterials.Polymer,53(9),1805–1822.

[0015] [8]Stephen J.EichhornRobert J.YoungGeoffrey R.Davies(2004).ModelingCrystal and Molecular Deformation in Regenerated Cellulose Fibers

[0016] [9]Ana Karina Marques Fortes Lustosa 1, Carla De Jesus Oliveira1,Patrick Veras Quelemes.(2017)In Situ Synthesis of Silver Nanoparticles in aHydrogel of Carboxymethyl Cellulose with Phthalated-Cashew Gum as a PromisingAntibacterial and Healing Agent.

[0017] The current problems of hydrogels are: (1) Agricultural water retaining agents are basically made of polyacrylamide, which pollutes the environment due to its difficulty in degradation. Polyaspartic acid can be used as a substitute for polyacrylamide due to its excellent degradation performance. (2) Although polyaspartic acid has excellent swelling properties, it has poor mechanical properties due to its low degree of cross-linking ( Figure 4 ), which greatly limits the application of polyaspartic acid in water retention agents. Summary of the invention

[0018] The technical problem to be solved by the present invention is to provide a method for preparing a polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent.

[0019] In order to solve the above technical problems, the present invention provides a method for preparing a polyaspartic acid-carboxymethyl cellulose physical and chemical cross-linked double network hydrogel (a method for preparing a polyaspartic acid-carboxymethyl cellulose double network hydrogel water-retaining agent), comprising the following steps:

[0020] 1) Preparation of polymer polysuccinimide;

[0021] 2) Preparation of polyaspartic acid-carboxymethyl cellulose hydrogel.

[0022] As an improvement of the preparation method of the present invention:

[0023] 1) Preparation of polymer polysuccinimide

[0024] 40-45 g (preferably 42.4 g) of phosphoric acid is added to 68-72 g (preferably 70 g) of aspartic acid (powder), and the mixture is uniformly mixed and then placed in a high temperature vacuum environment of 180-220° C. and 0.02-0.04 MPa (vacuum degree) for heat shrinkage polymerization reaction for 7-9 hours;

[0025] The obtained heat shrinkage polymerization product (powdered substance) is dissolved in dimethylformamide (excess dimethylformamide), heated in a water bath at 40 to 50° C. with magnetic stirring for 1.5 to 2.5 hours (to dissolve the heat shrinkage polymerization product), to obtain a solution of the heat shrinkage polymerization product;

[0026] Pour ethanol (excess ethanol) into the solution of the heat shrink polymerization reaction product, stand for stratification (standing time is at least 30 minutes), filter by suction, and dry the filter cake obtained by filtration to obtain polysuccinimide (powder);

[0027] 2) Preparation of polyaspartic acid-carboxymethyl cellulose hydrogel, the following steps are carried out in sequence:

[0028] 2.1) Dissolve 6 g of the polysuccinimide obtained in step 1) in a 1.8-2.2 M sodium hydroxide solution and stir magnetically for 0.5-1.5 h (to achieve the purpose of ring-opening the polysuccinimide); then adjust the pH to 4.5-5.0 to obtain a polyaspartic acid gel solution;

[0029] 2.2) Add 1-5 g (preferably 3 g) of carboxymethyl cellulose (CMC) to the polyaspartic acid gel solution and stir for 0.8-1.2 h, then add 2.8-3.2 g of ethylene glycol diglycidyl ether, and stir magnetically in a water bath at 45-55°C for 7-9 h to obtain a viscous gel mixture;

[0030] 2.3) Pour the viscous gel mixture obtained in step 2.2) into a mold and let it stand to form a gel.

[0031] As a further improvement of the preparation method of the present invention, step 1) is:

[0032] Divide phosphoric acid into 4 parts; take one part of phosphoric acid and add it to aspartic acid, mix evenly, place it in a high temperature vacuum environment for heat shrinkage polymerization reaction for 1.75 to 2.25 hours, then add the second part of phosphoric acid, continue to react in the high temperature vacuum environment for 1.75 to 2.25 hours, and so on, until the fourth part of phosphoric acid is added and the reaction is continued in the high temperature vacuum environment for 1.75 to 2.25 hours;

[0033] Therefore, the total heat shrink polymerization reaction time is 7 to 9 hours.

[0034] As a further improvement of the preparation method of the present invention, the step 1):

[0035] The dosage of dimethylformamide is 900-1100ml;

[0036] Ethanol: dimethylformamide = volume ratio of 1.4 to 16:1;

[0037] The rotation speed of the magnetic stirring was 300±50 rpm.

[0038] As a further improvement of the preparation method of the present invention, in the step 2.1), the amount of the sodium hydroxide solution is 35-40 mL (preferably 36 mL).

[0039] As a further improvement of the preparation method of the present invention, in the step 2.1): phosphoric acid is used to adjust the pH.

[0040] As a further improvement of the preparation method of the present invention, in step 2.2):

[0041] Add carboxymethyl cellulose (CMC) and stir at a speed of 500 ± 50 rpm;

[0042] After adding ethylene glycol diglycidyl ether, first stir the mixture in a water bath at a speed of 800±50 rpm for 1 h, and then stir the mixture in a water bath at a speed of 300±50 rpm for 6 to 8 h.

[0043] As a further improvement of the preparation method of the present invention, the standing time of step 2.3) is 5 to 7 hours.

[0044] The invention compounds polyaspartic acid and carboxymethyl cellulose (CMC), and adopts a hydrogen bond cross-linking method to further enhance the mechanical properties and water retention capacity of the gel. Meanwhile, the mechanical properties of the gel can be changed by adjusting the mass ratio of polyaspartic acid and carboxymethyl cellulose.

[0045] The present invention designs CMC to form a second network of a double network hydrogel (DN hydrogel) through hydrogen bond interaction, and then cross-links with ethylene glycol diglycidyl ether to form a first network of polyaspartic acid to prepare a DN hydrogel. The key problem of poor mechanical properties of PASP hydrogel is solved, and a hydrogel with excellent mechanical properties, swelling properties, water retention properties and biodegradability is designed, which has a wide range of uses.

[0046] Compared with the prior art, the present invention has the following advantages:

[0047] (1) Sea anemones and jellyfish can absorb a large amount of water and also cause excellent mechanical behavior due to subtle reversible non-covalent interactions in the body. To simulate these organisms, the present invention utilizes a physical cross-linking method (hydrogen bond interaction) to achieve the construction of polyaspartic acid-based DN hydrogels, thereby achieving the purpose of improving the mechanical properties of polyaspartic acid hydrogels while ensuring the water absorption and water retention properties of polyaspartic acid hydrogels.

[0048] (2) Most agricultural water-retaining agents are made of non-biodegradable polyacrylamide materials, while the present invention is prepared from two materials with good biodegradability (polyaspartic acid and carboxymethyl cellulose), which will not cause secondary pollution to the environment. At the same time, the raw materials are low-priced, providing a new idea for achieving sustainable development of modern agriculture.

[0049] In summary, the present invention uses polyaspartic acid and carboxymethyl cellulose to prepare a double network hydrogel, and obtains a double network hydrogel with excellent swelling properties, mechanical properties and water retention properties, which provides important technical parameters and reference materials for the development of hydrogels with excellent mechanical properties, swelling properties and water retention properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] The specific implementation modes of the present invention are further described in detail below with reference to the accompanying drawings.

[0051] Figure 1 Fourier infrared images of polyaspartic acid (PASP) and carboxymethyl cellulose (CMC) hydrogels with different ratios;

[0052] Figure 2 SEM images (A, B, C, G, H, I) and gel pore size diagrams (D, E, F, J, K, L) of polyaspartic acid and carboxymethyl cellulose hydrogels with different ratios;

[0053] Figure 3 This is a thermal stability analysis diagram of polyaspartic acid and carboxymethyl cellulose hydrogels with different ratios;

[0054] Figure 4 The compression performance diagram of polyaspartic acid and carboxymethyl cellulose hydrogels with different proportions:

[0055] Figure 4 middle:

[0056] A is the compression performance diagram of the hydrogel under 90% compression strain,

[0057] B is a schematic diagram of the compression cycle of the hydrogel under 90% compression strain.

[0058] C is the mechanical properties fitting toughness and modulus diagram of hydrogel under 90% compression strain,

[0059] D is the actual picture of hydrogel compression.

[0060] Figure 5 The tensile properties of polyaspartic acid and carboxymethyl cellulose hydrogels with different ratios are shown in Figure 2.

[0061] Figure 5 Middle: From left to right are the hydrogel tensile performance diagram, the schematic diagram of the hydrogel tensile strain and tensile stress data, and the hydrogel tensile fitting toughness and modulus diagram.

[0062] Figure 6 is a graph of swelling ratio and water content of polyaspartic acid and carboxymethyl cellulose hydrogels with different ratios;

[0063] Figure 6 middle:

[0064] Swelling process of PASP and PASP / CMC hydrogels in deionized water (A), 0.1 M urea solution (B), and 0.1 M NaCl solution (C);

[0065] First-order kinetic fitting of the swelling process of PASP and PASP / CMC hydrogels in deionized water (D), 0.1 M urea solution (E), and 0.1 M NaCl solution (F);

[0066] Second-order kinetic fitting of the swelling process of PASP and PASP / CMC hydrogels in deionized water (G), 0.1 M urea solution (H), and 0.1 M NaCl solution (I).

[0067] Figure 7 The water retention rate diagram of polyaspartic acid and carboxymethyl cellulose hydrogels with different ratios, that is, the centrifugal water retention performance diagram of the hydrogel at different rotation speeds (7000 rpm, 10000 rpm, 13000 rpm from left to right).

[0068] Figure 8 Biodegradation diagram of polyaspartic acid and carboxymethyl cellulose hydrogels with different ratios. DETAILED DESCRIPTION

[0069] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:

[0070] In the performance detection method of the present invention,

[0071] For thermogravimetry, please refer to Reena; Kumar, A.; Mahto, V.; Choubey, AKSynthesis and characterization of cross-linked hydrogels using polyvinyl alcohol and polyvinyl pyrrolidone and their blend for water shut-off treatments. Journal of Molecular Liquids 2020,301,112472.DOI: https: / / doi.org / 10.1016 / j.molliq.2020.112472.

[0072] For swelling, please refer to Liu, Y.; Hu, L.; Tan, B.; Li, J.; Gao, X.; He, Y.; Du, X.; Zhang, W.; Wang, W. Adsorption behavior of heavy metal ions from aqueous solution ontocomposite dextran-chitosan macromolecule resin adsorbent.Int J Biol Macromol2019,141,738-746.DOI:10.1016 / j.ijbiomac.2019.09.044From NLM Medline.

[0073] For centrifugal water retention, please refer to Lü, S.; Feng, C.; Gao, C.; Wang, X.; Xu, X.; Bai, X.; Gao, N.; Liu, M. Multifunctional Environmental Smart Fertilizer Based on l-Aspartic Acid for Sustained Nutrient Release. J. Agric. Food Chem. 2016, 64(24), 4965-4974. DOI: 10.1021 / acs.jafc.6b01133.

[0074] For biodegradation, please refer to Shi, S.; Wu, Y.; Wang, Y.; Yu, J.; Xu, Y. Synthesis and characterization of a biodegradable polyaspartic acid / 2-amino-2-methyl-1-propanol graft copolymer and evaluation of its scale and corrosion inhibition performance. RSC Advances 2017,7(58),36714-36721.DOI:10.1039 / c7ra06848d.

[0075] Embodiment 1, a method for preparing polysuccinimide, carrying out the following steps:

[0076] 1) Divide 42.4 g of phosphoric acid into 4 equal parts;

[0077] Take one part of phosphoric acid and add it to 70g of aspartic acid powder, mix them evenly, place them in a high temperature vacuum environment (200°C, 0.03MPa) for heat shrink polymerization reaction for 2 hours, then add the second part of phosphoric acid and continue to react for 2 hours in the above high temperature vacuum environment, and so on, until the fourth part of phosphoric acid is added and continue to react for 2 hours in the above high temperature vacuum environment;

[0078] That is, the total heat shrinkage polymerization reaction time was 8 hours.

[0079] The obtained heat shrinkage polymerization product (powdered substance) was dissolved in an excess amount (about 1000 ml) of dimethylformamide, and heated in a water bath with magnetic stirring for 2 h (water bath temperature was 45° C., speed was 300 rpm), until the heat shrinkage polymerization product was completely dissolved; and a solution of the heat shrinkage polymerization product was obtained;

[0080] Pour an excess amount (about 1500 ml) of ethanol into the solution of the heat shrink polymerization reaction product, let it stand for stratification (standing time is at least 30 minutes), filter it with suction, and dry the filter cake obtained by filtration (drying at 50° C. to constant weight) to obtain polysuccinimide (powder);

[0081] During the filtration process, when the pH of the filtrate reaches about 7 using pH test paper, it indicates that the filtration can be ended.

[0082] Example 2: A method for preparing a polyaspartic acid hydrogel, comprising the following steps:

[0083] 1) Dissolve 6 g of the dried polysuccinimide powder obtained in Example 1 in 36 mL of a 2M sodium hydroxide solution. After the polysuccinimide powder is completely dissolved, stir magnetically at 500 rpm for 1 h (to achieve the purpose of ring-opening of polysuccinimide); then adjust the pH to 4.8 with phosphoric acid to obtain a polyaspartic acid gel solution;

[0084] 2) Add 3 g of ethylene glycol diglycidyl ether to the polyaspartic acid gel solution obtained in step 1) and place in a 50° C. water bath and stir at 800 rpm for 1 h; a viscous gel is obtained (indicating that the cross-linking of PSI and EDGE is about to be completed), and then adjust the speed to 300 rpm and stir for another 7 hours;

[0085] 3) Pour 5 ml of the viscous gel mixture obtained in step 2) into a circular mold with a diameter of 1.5 cm for subsequent compression performance testing;

[0086] 5 ml of the viscous gel mixture obtained in step 2) was poured into a rectangular mold with a length and width of 10 cm×4 cm for subsequent tensile property measurement.

[0087] The mold was sealed with a plastic wrap and allowed to stand at room temperature for 6 hours to obtain polyaspartic acid hydrogel (PASP).

[0088] Example 3: A method for preparing a polyaspartic acid-carboxymethyl cellulose hydrogel, comprising the following steps:

[0089] 1) Same as step 1) of Example 2;

[0090] 2) Add 1 g of CMC to the polyaspartic acid gel solution obtained in step 1), stir at 500 rpm for 1 h, then add 3 g of ethylene glycol diglycidyl ether and place in a 50° C. water bath and stir at 800 rpm for 1 h; then adjust the speed to 300 rpm and stir for another 7 hours;

[0091] 3) Pour 5 ml of the viscous gel mixture obtained in step 2) into a circular mold with a diameter of 1.5 cm for subsequent compression performance testing;

[0092] 5 ml of the viscous gel mixture obtained in step 2) was poured into a rectangular mold with a length and width of 10 cm×4 cm for subsequent tensile property measurement.

[0093] The mold was sealed with a plastic wrap and allowed to stand at room temperature for 6 hours to obtain a polyaspartic acid-carboxymethyl cellulose hydrogel.

[0094] In this Example 3, the hydrogel is named PASP / CMC 6:1 .

[0095] Example 4: The amount of CMC added in Example 3 was changed from "1 g" to "2 g", and the rest was the same as Example 3. The hydrogel was named PASP / CMC 6:2 .

[0096] Example 5: The amount of CMC added in Example 3 was changed from "1 g" to "3 g", and the rest was the same as Example 3. The hydrogel was named PASP / CMC 6:3 .

[0097] Example 6: The amount of CMC added in Example 3 was changed from "1 g" to "4 g", and the rest was the same as Example 3. The hydrogel was named PASP / CMC 6:4 .

[0098] Example 7: The amount of CMC added in Example 3 was changed from "1 g" to "5 g", and the rest was the same as Example 3. The hydrogel was named PASP / CMC 6:5 .

[0099] The hydrogels (PASP / CMC) obtained in Examples 3 to 7 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ), as well as the hydrogel (PASP) obtained in Example 2 as a control, the polysuccinimide (PSI) obtained in Example 1, and carboxymethyl cellulose (CMC) were freeze-dried (freeze-dried at -80°C for 48 hours); the corresponding freeze-dried products were obtained and the following experiments 1 to 3 were carried out.

[0100] Experiment 1, Fourier infrared spectroscopy:

[0101] The above freeze-dried products (PASP, PASP / CMC 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC6:5 ) was detected by Fourier transform infrared spectrometer (FTIR), and the obtained Fourier infrared image was as follows: Figure 1 described.

[0102] according to Figure 1 , we can know that:

[0103] Polyaspartic acid can form the first layer of network through covalent interaction, and carboxymethyl cellulose can form the second layer of network through hydrogen bonding interaction. Carboxymethyl cellulose can enhance the tightness between the two layers of network through hydrogen bonding interaction.

[0104] Experiment 2, Scanning Electron Microscope:

[0105] The above freeze-dried products (PASP, PASP / CMC 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ) was detected by scanning electron microscopy (SEM), and the obtained SEM images are shown in Figure 2 described.

[0106] according to Figure 2 , we can know that:

[0107] From the SEM surface image, it can be seen that a loose network structure is formed on the surface of the PASP hydrogel, while after the addition of CMC, the hydrogel forms a denser network structure, making the gel network more uniform and porous.

[0108] In summary, infrared spectroscopy and scanning electron microscopy indicate that there is interaction between polyaspartic acid and carboxymethyl cellulose in the present invention.

[0109] Experiment 3, thermal stability:

[0110] The above freeze-dried products (PASP, PASP / CMC 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ) for thermal stability testing; analysis chart as shown Figure 3 described.

[0111] according to Figure 3 , we can know that:

[0112] The weight loss of the gel after adding carboxymethyl cellulose was significantly reduced compared with that of polyaspartic acid, indicating that the interaction between carboxymethyl cellulose and polyaspartic acid can effectively improve the thermal stability of the gel.

[0113] Experiment 4: Compression performance test:

[0114] The hydrogels (PASP / CMC) obtained in Examples 3 to 7 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ), and the hydrogel (PASP) obtained in Example 2 as a control were subjected to compression performance testing using a texture analyzer (the test parameter set was adjusted to 90% compression deformation), and the results obtained are as follows: Figure 4 described.

[0115] according to Figure 4 , we can know that:

[0116] The compression performance of PASP hydrogel is only 41 kPa at 90% strain, and PASP / CMC 6:5 At 90% strain, it is 1193 kPa, which is 29 times that of PASP hydrogel. The compression performance of the hydrogel gradually increases with the increase of CMC content. At the same time, the modulus also increases, proving that the double network structure formed between PASP and CMC improves the mechanical properties of the gel.

[0117] Experiment 5: Tensile performance test

[0118] The hydrogels (PASP / CMC) obtained in Examples 3 to 7 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ), and the hydrogel (PASP) obtained in Example 2 as a control were subjected to tensile property testing using a texture analyzer (the test parameter set was that the tensile deformation was set to 1000%, which could break the gel), and the results were as follows: Figure 5 described.

[0119] according to Figure 5 , we can know that:

[0120] The tensile properties of PASP hydrogel alone are the worst, and the tensile instrument cannot sense it. With the gradual increase of CMC content, its fracture length and tensile stress increased from 298% and 0.697 kPa to 530% and 2.660 kPa. At the same time, the elastic modulus and toughness of the gel also increased from 274.65 Pa and 0.1428 kJ·m-3 to 510.94 Pa and 0.8035 kJ·m-3. This shows that after gradually adding CMC, more CMC will interact with PASP to enhance the fracture tensile stress and toughness of the gel.

[0121] Experiment 6: Swelling performance test:

[0122] The hydrogels (PASP / CMC) obtained in Examples 3 to 7 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ), and the hydrogel (PASP) obtained in Example 2 as a control were tested for water content and swelling rate. The results are as follows Figure 6 described.

[0123] according to Figure 6 It can be seen that the water content of PASP alone is 65%, and with the increase of CMC content, the water content gradually decreases to 57%. This shows that in addition to the network structure generated by the gel after PASP cross-linking, a new network structure is formed after adding CMC, making the gel network structure more compact, thereby reducing the water content.

[0124] The water absorption performance of the PASP hydrogel alone reached the best at 70 hours, which was 57 g / g. As the CMC ratio increased, the swelling rate of the hydrogel gradually decreased. This indicates that the increase in the CMC ratio will form a denser hydrogen bond network inside the gel, and the network is difficult to continue to expand during the swelling process, which reduces the water absorption performance of the gel.

[0125] Experiment 7: Centrifugal water retention performance test

[0126] The hydrogels (PASP / CMC) obtained in Examples 3 to 7 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ), and the hydrogel (PASP) obtained in Example 2 as a control were tested for centrifugal water retention performance.

[0127] according to Figure 7 It can be learned that:

[0128] The water retention rate of PASP at 7000rpm for 60min is 86%, while at 13000rpm for 60min, the water retention rate of PASP is only 47%. This shows that the water retention performance of PASP decreases rapidly with the increase of pressure, because its loose network structure cannot lock the water in the gel well. As for PASP / CMC hydrogel, the water retention performance decreases slightly with the change of pressure, but it does not decrease much compared with PASP, which proves that the gradually dense gel network can lock the water inside the gel well under different pressures, thereby improving the water retention of the gel.

[0129] Experiment 8: Degradation experiment

[0130] The hydrogels (PASP / CMC) obtained in Examples 3 to 7 6:1、 PASP / CMC 6:2、 PASP / CMC 6:3、 PASP / CMC 6:4、 PASP / CMC 6:5 ), and the hydrogel (PASP) obtained in Example 2 as a control were subjected to degradation experiments.

[0131] according to Figure 8 It can be learned that:

[0132] PASP hydrogel degraded by 95% in 28 days, and the addition of CMC delayed the degradation of the hydrogel, allowing the hydrogel to be reused for a long time.

[0133] In summary, the polyaspartic acid carboxymethyl cellulose hydrogels obtained in Examples 3 to 7 exhibit excellent mechanical properties, swelling properties, water retention properties and biodegradability.

[0134] The present invention constructs a double network hydrogel by adding CMC to the PASP system. By comparing the mechanical properties of PASP and PASP / CMC hydrogels, it can be seen that the compressive stress of PASP is only 41 kPa at 90% strain, while that of PASP / CMC is 6:3 At 90% strain, its compressive stress is 832 kPa, which is 20.3 times that of PASP hydrogel. As above, due to the soft nature of PASP, the texture analyzer cannot sense its tensile stress, while PASP / CMC 6:3 Its tensile strain is 465% and its tensile stress is 1.5 kPa, which indicates that the addition of CMC and the construction of a double-network hydrogel system can greatly improve the mechanical properties of the hydrogel.

[0135] By adding CMC to the PASP system to construct a double network hydrogel, and comparing the swelling properties of PASP and PASP / CMC hydrogels, it can be seen that after adding CMC, the swelling properties of the hydrogel decreased. This is because the cross-linked hydrogen bond network formed between CMC and the PASP network forms a double network hydrogel. The tight network structure will reduce the swelling properties. CMC contains a large number of hydrophilic hydroxyl and carboxyl groups, which allows it to retain its original swelling properties to a greater extent while constructing a double network hydrogel.

[0136] By adding CMC to the PASP system to construct a double network hydrogel, and comparing the water retention performance of PASP and PASP / CMC hydrogel, it can be seen that under the action of high-speed centrifugation, the water retention performance of PASP decreases rapidly, and its loose network structure cannot lock in moisture well. After adding CMC, due to the formation of its double network, its dense network structure can lock in the moisture inside it well under high pressure, thereby improving the water retention performance of the hydrogel.

[0137] By adding CMC to the PASP system to construct a double network hydrogel, and comparing the biodegradability of PASP and PASP / CMC hydrogels, it can be seen that PASP is easily decomposed by microorganisms due to its loose structure. Although CMC is also a degradable material, the dense network structure slows down the biodegradation rate of the hydrogel.

[0138] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.

Claims

1. A method for preparing a polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent, characterized in that The following steps are involved: 1) Preparation of polymer polysuccinimide; 2) Preparation of polyaspartic acid-carboxymethyl cellulose hydrogel.

2. The method for preparing the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to claim 1, characterized in that: 1) Preparation of polymer polysuccinimide Add 40-45g of phosphoric acid to 68-72g of aspartic acid and mix evenly, then place in a high temperature vacuum environment of 180-220°C and 0.02-0.04Mpa for heat shrink polymerization reaction for 7-9 hours; The obtained heat shrinkage polymerization product is dissolved in dimethylformamide, heated in a water bath at 40 to 50° C. with magnetic stirring for 1.5 to 2.5 hours to obtain a solution of the heat shrinkage polymerization product; Pour ethanol into the solution of the heat shrink polymerization reaction product, let it stand for stratification, filter it with suction, and dry the filter cake obtained by filtration to obtain polysuccinimide; 2) Preparation of polyaspartic acid-carboxymethyl cellulose hydrogel, the following steps are carried out in sequence: 2.1) Dissolve 6 g of the polysuccinimide obtained in step 1) in a 1.8-2.2 M sodium hydroxide solution and stir magnetically for 0.5-1.5 h; then adjust the pH to 4.5-5.0 to obtain a polyaspartic acid gel solution; 2.2) Add 1-5 g of carboxymethyl cellulose to the polyaspartic acid gel solution and stir for 0.8-1.2 h, then add 2.8-3.2 g of ethylene glycol diglycidyl ether, and stir magnetically in a water bath at 45-55°C for 7-9 h to obtain a viscous gel mixture; 2.3) Pour the viscous gel mixture obtained in step 2.2) into a mold and let it stand to form a gel.

3. The preparation method of the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to claim 2, characterized in that The step 1) is: Divide phosphoric acid into 4 parts; take one part of phosphoric acid and add it to aspartic acid, mix evenly, place it in a high temperature vacuum environment for heat shrinkage polymerization reaction for 1.75 to 2.25 hours, then add the second part of phosphoric acid, continue to react in the high temperature vacuum environment for 1.75 to 2.25 hours, and so on, until the fourth part of phosphoric acid is added and the reaction is continued in the high temperature vacuum environment for 1.75 to 2.25 hours; Therefore, the total heat shrink polymerization reaction time is 7 to 9 hours.

4. The method for preparing the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to claim 2 or 3, characterized in that The step 1): The dosage of dimethylformamide is 900-1100ml; Ethanol: dimethylformamide = volume ratio of 1.4 to 16:1; The rotation speed of the magnetic stirring was 300±50 rpm.

5. The method for preparing the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to claim 4, characterized in that In the step 2.1), the amount of sodium hydroxide solution used is 35-40 mL.

6. The method for preparing the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to claim 5, characterized in that In the step 2.1), the pH is adjusted with phosphoric acid.

7. The method for preparing the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to claim 6, characterized in that In the step 2.2): Add carboxymethyl cellulose and stir at a speed of 500 ± 50 rpm; After adding ethylene glycol diglycidyl ether, first stir the mixture in a water bath at a speed of 800±50 rpm for 1 h, and then stir the mixture in a water bath at a speed of 300±50 rpm for 6 to 8 h.

8. The method for preparing the polyaspartic acid-carboxymethyl cellulose double network hydrogel water retaining agent according to any one of claims 2 to 7, characterized in that: The standing time of step 2.3) is 5 to 7 hours.

Citation Information

Patent Citations

  • Preparation method of polyaspartic acid semi-interpenetrating nano composite hydrogel

    CN113004545A

Cited By

  • Preparation method of polyaspartic acid-carboxymethyl cellulose hydrogel-stearic acid-urea slow-release fertilizer

    CN121342593A